Object-oriented paradigm as a method for formalizing character properties in fictional universes (on the example of the character representation of Nekhlyudov in Leo Tolstoy’s novel Resurrection) - Skomorovskiy, Grigory (Vilnius University Open Series, 2024)
The article explores the possibility of applying the object-oriented paradigm (a term sourced from computer science) to formalize various implementations of characters in fictional universes. Examples are provided based on the implementations of the character of Nekhlyudov from Tolstoy’s novel Resurrection. Possible applications of the discussed approach are examined for analyzing the relationships between different implementations of the same character, as well as for generating new characters based on the individual preferences of the reader (or viewer, user).